Comprehensive Treatment of Facial Deformity Due to Radiotherapy in Rhabdomyosarcoma Patients: Distraction Osteogenesis and Free Flaps Surgical Technique. Issue 4 (June 2019) - Bianchi, Alberto; Crimi, Salvatore; Cipriani, Riccardo; De Ponte, Francesco Saverio; Cicciù, Marco; Marchetti, Claudio
Abstract : Abstract: Radiotherapy is essential for achieving and maintaining local control in head and neck rhabdomyosarcoma patients. However, radiotherapy may cause outgrowth disturbances of facial bone and soft tissue, resulting in facial asymmetry. Several studies have shown that the management of irradiated bones still remains challenging. The possibility of obtaining functional and aesthetic results when managing facial deformities due to radiation therapy with distraction osteogenesis combined with free flaps reconstruction is not common and not well documented in recent literature. In this report, we present the long-term results of distraction osteogenesis and soft tissue reconstruction via microvascular free flap to correct the facial hypoplasia of a young patient who underwent radiation therapy for rhabdomyosarcoma. This is the first presentation of 26 years long-term results in a patient who also underwent free flaps reconstruction as ancillary surgery for esthetic good results.